2020
DOI: 10.1101/2020.11.11.378364
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zona Incerta subpopulations differentially encode and modulate anxiety

Abstract: Despite recent clinical observations linking the Zona Incerta (ZI) to anxiety, little is known about whether and how the ZI processes anxiety. Here, we subject mice to anxious experiences and observe an increase in ZI cfos-labelled neurons and single-cell calcium activity as well as an efficient effect of ZI infusion of diazepam a classical anxiolytic drug. We further identify that somatostatin-(SOM), calretinin-(CR), and vesicular glutamate transporter-2 (Vglut2)-expressing cells display unique electrophysiol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…Recently, Kelly Tan's lab reported the involvement of SST-positive neurons in the ZI in the regulation of anxiety behavior [12]. They found that the SST-positive neurons in the ZI are activated when mice are in anxiety-inducing environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Kelly Tan's lab reported the involvement of SST-positive neurons in the ZI in the regulation of anxiety behavior [12]. They found that the SST-positive neurons in the ZI are activated when mice are in anxiety-inducing environment.…”
Section: Discussionmentioning
confidence: 99%
“…The zona incerta (ZI), originally described as a "zone of uncertainty" [1], consists of heterogeneous neuron subtypes and extensive efferent and afferent projections connected with various regions across the brain [2]. Recent studies have revealed the involvement of the ZI in various functions including binge-like eating [3], hunting [4,5], sleep [6], parkinsonian motor symptoms [7], fear learning and fear memory [8][9][10][11], anxiety [12], and novelty-seeking [13], as well as neuron development [14]. These behaviors are closely associated with physiological functions that are beneficial for the well-being and survival of animals [15].…”
Section: Introductionmentioning
confidence: 99%
“…Using mice that express ChR2-eYFP in dACC→PnC neurons, we photostimulated axon collaterals within the zona incerta (ZI; Fig. 4f), a brain region known to regulate fear-and anxiety-related responses in mice 27,28 . This did not affect anxiety-like behavior in the elevated plus maze test (Fig.…”
Section: The Dacc→pnc Circuit Alleviates Anxiety-like Behaviorsmentioning
confidence: 99%
“…The subthalamic zona incerta (ZI) is an enigmatic inhibitory brain region that integrates multisensory information and regulates a wide range of behaviors including learning (Ahmadlou et al, 2021; Li et al, 2021; Liu et al, 2017; Masri et al, 2009; Zhang and van den Pol, 2017; Zhou et al, 2018). Since this area orchestrates cortical development in neonatal mice through LRI afferents to L1 (Chen and Kriegstein, 2015), we asked whether a similar projection is present in adult auditory cortex (ACx).…”
Section: Main Textmentioning
confidence: 99%
“…Despite the therapeutic capacity of the ZI (Ossowska, 2020), and its central involvement in numerous behaviors including sleep (Liu et al, 2017), feeding (Zhang and van den Pol, 2017), pain (Masri et al, 2009), novelty-seeking (Ahmadlou et al, 2021), anxiety (Li et al, 2021) and threat memory (Zhou et al, 2018), the function and information content of its projection to neocortex has remained elusive. This study identifies LRI ZI afferents as a source of remarkably precise auditory information and reinforcement signals in ACx which selectively connect to INs, widely integrate information from across the neuroaxis, are essential for associative memory and undergo complex, bidirectional plasticity during and after learning.…”
Section: Main Textmentioning
confidence: 99%